Palatability of drinking water : effects on drinking behaviour, hydration status and performance in university male basketball players - Taim, Bernadette Cherianne (Nanyang Technological University, 2019)
Background: Exercise-related dehydration may impair athletic performance in the heat. Promoting fluid intake to correct fluid deficits can minimise the adverse effects of hypohydration and fluid palatability can influence drinking behaviour. While studies have been conducted on the effects of flavoured carbohydrate-electrolyte drinks on voluntary drinking, few have considered the use of colourless carbohydrate-free flavoured water (FW). Purpose: This study aims to examine the differences in voluntary fluid intake of FW and unflavoured water (UW), and its effects on hydration status and basketball performance. Method: 18 male university basketball players (age 23.1 ± 1.3 years) performed 3 periods of 10-min 3×3 full court basketball game, separated by 5-min rest breaks, in an open-air sheltered basketball court (31.7 ± 0.5°C, 61.8 ± 3.7% RH). The participants were randomly assigned either FW or UW (4.5 ± 0.8°C). Drinking was ad libitum. Fluid intake, hydration measures and performance variables were assessed. Results: There were no significant differences in voluntary fluid intake, hydration status and basketball performance between FW and UW (p > 0.05). Significant correlations were observed for hydration measures and performance variables (p < 0.05). Conclusion: Carbohydrate-free FW does not enhance voluntary fluid intake, hydration status and performance in male basketball players. Regardless of the type of fluid available, the participants could self-regulate adequately (≤2% changes in body mass). Future studies may prolong exposure time to exercise and examine the effects of artificial sweeteners on palatability and brain responses during exercise.